RESILIENCE AND TRAUMA IN “WHERE THE CRAWDADSSING” - Tri Marlinna, Dhui Ayu; Ernawati, Asih; Riyatno, Riyatno (DE FACTO : Journal Of International Multidisciplinary Science, 2025)
This study examines the psychological struggles of Kya, the protagonist of Where the Crawdads Sing, focusing on her experience with Post-Traumatic Stress Disorder (PTSD) and the defense mechanisms she employs to survive. As a child abandoned by her family and ostracized by society, Kya develops psychological responses shaped by isolation and trauma. Using psychological literary criticism, this study analyzes how PTSD symptoms manifest in Kya’s behavior, such as hypervigilance, emotional detachment, and avoidance. Additionally, it explores her defense mechanisms, including repression, denial, and intellectualization, as means of coping with her traumatic past. The findings suggest that Kya’s psychological struggles reflect a broader theme of resilience in the face of adversity. By examining her journey, this research highlights the impact of abandonment and societal rejection on mental health. This study contributes to the discussion of trauma representation in literature, emphasizing the intricate relationship between psychological defense mechanisms and survival.